Perception and experiences of sexual harassment among women working in hospitality workplaces of Bahir Dar city, Northwest Ethiopia: a qualitative study - Mulugeta Dile Worke; Zewdie Birhanu Koricha; Gurmesa Tura Debelew (BMC, 2021)
Abstract Background Workplace sexual harassment is a public health problem that depends on gender, context, and perceived ideology. Although studies have documented the prevalence and consequences of workplace sexual harassment worldwide, victims' perceptions and experiences are still poorly understood in low and middle-income countries, particularly Ethiopia. Female workers in the hospitality industry, including hotels, bars, restaurants, fast-food restaurants, and cafeterias, are particularly affected. Hence, this study aimed to explore sexual harassment perceptions and experiences among women working in these workplaces. Methods An exploratory qualitative study was conducted from 1 January to 30 August 2019. Data were collected from female employees and key informants from several hospitality workplaces in Bahir Dar City. Data were collected through focus group discussions, in-depth interviews, and key-informant interviews. Women who experienced sexual harassment were selected using the snowball method, and key informants were recruited purposefully. Six focus group discussions, ten in-depth interviews, and thirteen key informant interviews were conducted. Data were analysed using the ATLAS ti version 8.4.24. Results In this study, most participants perceived that sexual harassment is pressuring, threatening, touching, abducting sexual advances, and experiencing verbal, physical, and non-verbal types. Similarly, the perceived risk factors were related to the organisations, the customers, and the victims, with the consequences being work-related, health-related, financial-related, and family-related. Conclusions Workplace sexual harassment in hospitality workplaces is poorly understood, but many women experience it. A variety of factors also caused it, and it influenced both organisations and people. Public awareness programs, pre-service preparation, in-service training, prevention, and psychosocial support are needed. Similarly, policies and strategies for the organisations should be developed and implemented.